Building trust at work with Amy Brann (Assemble You, 2023)
In this episode, Adam speaks to founder and CEO of Synaptic Potential, Amy Brann. Amy is a published author and a keynote speaker, and in this podcast she gives some fascinating insights into the importance of trust at work, and how you can build it - or break it.